The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7860/jcdr/2022/52095.16062
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Factors Affecting Patient Safety in the Emergency Department: A Retrospective Study

Abstract: Introduction: Emergency Departments (EDs) have been described as complex, dynamic and at high risk for medical errors. Factors affecting the risk of medical error in the ED are related to communication, triage and medication management and upto 3% of all medical errors in hospitals take place in the ED. Aim: To identify the factors affecting patients' safety in the EDs of two major hospitals in Taif city based on Occurrence Variance Reporting (OVR). Materials and Methods: The present study was a crosssection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, they learn to follow the process after filling out an OVR form, starting with their supervisor. According to Althobaiti et al, 2022 study, OVR is important for attaining patient and staff safety, enhancing care quality, and lowering medical mistakes or accidents suggested that medical workers, especially nurses, need to be more aware of the significance of reporting all incidences. Findings from a study by Albarrak et al (2020) showed that although participants thought reporting took a lot of time, most felt that training-related OVR knowledge and skills were sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they learn to follow the process after filling out an OVR form, starting with their supervisor. According to Althobaiti et al, 2022 study, OVR is important for attaining patient and staff safety, enhancing care quality, and lowering medical mistakes or accidents suggested that medical workers, especially nurses, need to be more aware of the significance of reporting all incidences. Findings from a study by Albarrak et al (2020) showed that although participants thought reporting took a lot of time, most felt that training-related OVR knowledge and skills were sufficient.…”
Section: Discussionmentioning
confidence: 99%